Research on Stepless Speed Change Mechanism of Variable Diameter Pulley and Planetary Compound Transmission - Chuang Yan; Aiping Song; Jianzhou Pan; Ning Mei (Jixie chuandong)
A high-efficiency and high-power continuously variable transmission（CVT） is studied, which is mainly composed of variable-diameter pulley stepless speed change transmission and planetary differential gear train transmission. Multi-channel transmission and power convergence can be realized through the combination of variable-diameter pulley transmission and planetary gear transmission, and the ratio of power convergence can be adjusted through the free ratio of two input speeds of planetary differential gear train. The mechanism has the characteristics of simple structure, high transmission power, high efficiency transmission and stable operation.